2018
DOI: 10.1111/cns.12821
|View full text |Cite
|
Sign up to set email alerts
|

Myt1l induced direct reprogramming of pericytes into cholinergic neurons

Abstract: Our findings provided proof of the principle that cholinergic neurons could be produced from HBVPs by reprogramming factor-mediated fate instruction. Myt1l was a critical mediator of induced neuron cell reprogramming. HBVPs represent another excellent alternative cell resource for cell-based therapy to treat neurodegenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Given that astrocyte reactivity is a hallmark of the pathological CNS, RA-derived cholinergic neurons might be potential targets for the treatment of neurodegenerative diseases. Recently, Liang et al reported that MYT1L could directly reprogram human brain vascular pericytes into cholinergic neurons [72], indicating the Myt1l expression in our experiments might be essential for converting and maintaining the cholinergic neuron phenotype. Although these mechanisms remained to be further explored, we believe that the different effects depended on our unique induction cocktail.…”
Section: Discussionmentioning
confidence: 56%
“…Given that astrocyte reactivity is a hallmark of the pathological CNS, RA-derived cholinergic neurons might be potential targets for the treatment of neurodegenerative diseases. Recently, Liang et al reported that MYT1L could directly reprogram human brain vascular pericytes into cholinergic neurons [72], indicating the Myt1l expression in our experiments might be essential for converting and maintaining the cholinergic neuron phenotype. Although these mechanisms remained to be further explored, we believe that the different effects depended on our unique induction cocktail.…”
Section: Discussionmentioning
confidence: 56%
“…We next replaced NEUROG2 with ASCL1, since both of them work as pioneer transcription factors dominantly controlling gene expression and neuronal fates [29,30]. Furthermore, ASCL1 + progenitors can give rise to cholinergic neurons [23,[31][32][33].…”
Section: Rapid and Efficient Generation Of Hibfcns From Adult Human Smentioning
confidence: 99%
“…As pericytes have pluripotent individualities, so they have the capacity to trans-differentiate into other cell types such mesenchymal lineage [ 21 , 22 ], neurons, astrocytes, and oligodendrocytes [ 22 , 29 , 104 ]. Type A pericytes, but not types B, participate in scar tissue formation after spinal cord injury.…”
Section: Pericytes Restorative and Stem Cell-like Behavior In Bbb Recmentioning
confidence: 99%